2022
DOI: 10.3389/fmolb.2022.785232
|View full text |Cite
|
Sign up to set email alerts
|

Multiplatform Metabolomics Studies of Human Cancers With NMR and Mass Spectrometry Imaging

Abstract: The status of metabolomics as a scientific branch has evolved from proof-of-concept to applications in science, particularly in medical research. To comprehensively evaluate disease metabolomics, multiplatform approaches of NMR combining with mass spectrometry (MS) have been investigated and reported. This mixed-methods approach allows for the exploitation of each individual technique’s unique advantages to maximize results. In this article, we present our findings from combined NMR and MS imaging (MSI) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…Inductively coupled plasma mass spectrometry (ICP‐MS) can provide elemental analysis and detect the presence of salts, metals, and metalloids that would be difficult by other methods 37 . MS‐based metabolomics imaging provides spatial distribution of metabolites, but it has low throughput and requires large tissue or cell samples because of the relatively low resolution (50–200 μm) 38 . MS imaging also creates large data sets, easily a terabyte or more per sample, which makes statistical analysis using standard software packages impractical.…”
Section: A Multiplatform Approach Addresses Single Platform Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inductively coupled plasma mass spectrometry (ICP‐MS) can provide elemental analysis and detect the presence of salts, metals, and metalloids that would be difficult by other methods 37 . MS‐based metabolomics imaging provides spatial distribution of metabolites, but it has low throughput and requires large tissue or cell samples because of the relatively low resolution (50–200 μm) 38 . MS imaging also creates large data sets, easily a terabyte or more per sample, which makes statistical analysis using standard software packages impractical.…”
Section: A Multiplatform Approach Addresses Single Platform Limitationsmentioning
confidence: 99%
“…37 MS-based metabolomics imaging provides spatial distribution of metabolites, but it has low throughput and requires large tissue or cell samples because of the relatively low resolution (50-200 μm). 38 MS imaging also creates large data sets, easily a terabyte or more per sample, which makes statistical analysis using standard software packages impractical.…”
Section: A Multiplatform Approach Addresses Single Platform Limitationsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Uniformly 13 C-labeled Orn (L-ornithine: HCl, [U- 13 C 5 ]Orn, 98%) was purchased from Cambridge Isotope Laboratories, Inc. (Tewksbury, MA, USA). The Orn to Spm bio-synthesis pathway is illustrated in Figure 1 with 13 C propagation from [U- 13 C 5 ]Orn to [4,[5][6][7][8][9][10][11][12][13] C 2 ]Spm indicated, and 13 C and 1 H chemical shift values labeled in the diagram.…”
Section: Animals and Materialsmentioning
confidence: 99%
“…Using high‐resolution magic angle spinning NMR and mass spectrometry imaging, we have previously demonstrated that the observed Spm is concentrated in the healthy and histologically benign (without histological evidence of malignancy) epithelia of human prostate tissue 7,8 . We further used laser‐capture‐microdissection and real‐time qPCR to measure mRNA expression of the rate‐limiting enzyme in Spm bio‐synthesis, ornithine decarboxylase (ODC), in captured cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation